2023
DOI: 10.1128/spectrum.03349-22
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CMY Variant Confers Transferable High-Level Resistance to Ceftazidime-Avibactam in Multidrug-Resistant Escherichiacoli

Abstract: Ceftazidime-avibactam is a novel β-lactam–β-lactamase inhibitor (BLBLI) combination with powerful activity against Enterobacterales isolates producing AmpC, such as CMY-like cephalosporinase. However, in recent years, CMY variants have been reported to confer ceftazidime-avibactam resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A similar expansion of the substrate binding site is observed in AmpC Ent385 , which contains the deletion of residues A294 and P295 and also confers reduced susceptibility to cefiderocol ( 6 , 15 ). In addition, CMY-172 and CMY-178 contain the deletion of three residues K290, V291, and A292 on the R2 loop, resulting in the higher MICs of 16 and 64 mg/L for ceftazidime-avibactam, respectively, and 1 mg/L for cefiderocol ( 30 ). Moreover, our results indicated that the CMY-2-like β-lactamases strongly recognize cefiderocol compared to the other β-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…A similar expansion of the substrate binding site is observed in AmpC Ent385 , which contains the deletion of residues A294 and P295 and also confers reduced susceptibility to cefiderocol ( 6 , 15 ). In addition, CMY-172 and CMY-178 contain the deletion of three residues K290, V291, and A292 on the R2 loop, resulting in the higher MICs of 16 and 64 mg/L for ceftazidime-avibactam, respectively, and 1 mg/L for cefiderocol ( 30 ). Moreover, our results indicated that the CMY-2-like β-lactamases strongly recognize cefiderocol compared to the other β-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhou et al, is a new CMY variation that mediates high-level resistance to ceftazidime-avibactam by improving ceftazidime hydrolysis and decreasing avibactam affinity. Notably, high-frequency horizontal transmission of bla CMY-178 was possible without incurring fitness costs (Zhou et al, 2023). In addition, a recent study by Hernańdez-Garcıá et al found that strains of E. coli with the KPC-49 variant were resistant to ceftazidime/avibactam.…”
Section: Ceftazidime-avibactammentioning
confidence: 99%
“…Recent studies have demonstrated antibiotic resistance against combination therapies involving the latest BLIs and against new β-lactams, such as durlobactam [28], relebactam [29,30], zidebactam [31], tazobactam [32], taniborbactam [33], thiol-containing BLIs under development [34], and cefiderocol [35]. The resistance mechanisms include upregulation of efflux, mutations in the β-lactam target PBPs, and expression of β-lactamases and mutants less susceptible to the specific BLI, such as KPC-109 [36], NDM-9 [33], IMP-6 [34], and CMY-178 [37]. These resistance mutants highlight the need for the antimicrobial field to constantly explore novel inhibitor chemotypes to counter future resistance.…”
Section: Targeting β-Lactamases: Innovative Technologies and Promisin...mentioning
confidence: 99%